Direct, Moderating and Mediating Effects of Market Orientation on the Performance of Airports in Europe's Peripheral Areas - Halpern, Nigel; Pagliari, Romano (Haworth Press, 2008)
As a consequence of deregulation in the airline industry, market forces rather than public service considerations increasingly dictate routes serving airports in Europe's peripheral areas. The new market advocates market-driven management practices as a means of satisfying airline customers and implies that airports that adopt a more market-orientated approach than their rivals will perform better. This study investigates the relationship between market orientation and the performance of airports in Europe's peripheral areas. The research strategy was implemented using a questionnaire-based survey that was sent by email to managers at 214 airports. Usable responses from 84 airports were received and analysed. The findings demonstrate that market orientation has a significant and positive effect on performance, which is moderated by high levels of market turbulence and a focus on developing leisure services. The findings also demonstrate that the relationship between market orientation and performance is mediated by innovative marketing practices. The paper concludes with some implications for airport managers and recommendations for future research.
Keywords: Market orientation performance airports Europe's peripheral areas